The Surrender of Tobruk in 1942: Press reports and soldiers’ memories - Horn, Karen; Katz, David (Scientia Militaria - South African Journal of Military Studies, 2016)
Most quarters of the Allied camp greeted the fall of Tobruk on 21 June 1942 with incredulity. The epitome of a heroic defence conducted the year before had now deteriorated into a military debacle, resulting in thousands of Allied soldiers sent ‘into the bag’. The enormity of the defeat, at first greeted in muted fashion by a stunned press, soon turned into outrage at yet another Allied military fiasco. The British and South African papers began to demand answers from politicians and military leaders for this shocking and unexpected catastrophe. The press, normally sensitive to maintaining positive home front morale, discarded their wartime cosseting approach and embarked on a quest to find a scapegoat. Those captured at Tobruk were equally outraged that their freedom had been traded cheaply with hardly a fight. To many of these prisoners of war, the blame for their ignominious surrender rested squarely with the fortress commander, Major General HB Klopper. It was of little consequence to those now languishing behind the wire that the reasons for defeat were much more intricate and went beyond the performance of one man. This article examines a selection of representative press reports in the weeks immediately preceding and following the rout, and the oral reminiscences of former prisoners-of-war taken at Tobruk, which together, have contributed towards an enduring memory of the so-called Tobruk ‘debacle’.